Load angle estimation of synchronous generator - Veinović, Slavko S; Janda, Zarko; Stojic, Djordje; Dragosavac, Jasna; Joksimovic, Dusan; Klasnic, Ilija; Djordjevic, Milan (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
In this paper a load angle estimation method of round rotor synchronous generator is presented for load angle limiter in AVR systems design purpose. To get information of load angle it is necessary to have values of the one terminal voltage, one phase current and q-axis reactance Xq. Mentioned values are acquired by synchronous sampling and processed by discrete Fourier transformation. The accuracy of presented method highly depends on quality of zero-crossing detection of the input voltage signal and on the calculation of the fundamental frequency. This method is of reduced sensitivity to higher harmonics presence in voltages and currents. Another advantage, when compared to other dq or αβ based calculations, is the necessity of use only two measurement channels. Drawback of described approach is lack of immunity to current asymmetry. However, solution to overcome this problem is offered by introducing the additional measurements into the algorithm to extract the synchronous sampled direct components of three phase currents.
Keywords: estimation; synchronous generator; load angle; zero crossing; discrete Fourier transform